Struktur Transposisi-Transformasi Tafsir: Perubahan Al-Iklīl ke Tāj al-Muslimīn karya Misbah Musthofa (w.1994) - Jamal, Muhammad Badrul (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This article traces the evolution of KH Misbah Musthofa’s exegetical method by comparing al-Iklīl fī Maʿānī al-Tanzīl (1983) with Tāj al-Muslimīn (1988) on the seven verses of QS. al-Fātiḥah. Addressing a research gap that has hitherto focused only on locality or intertextuality, this qualitative-descriptive study extracts the original Javanese-Pegon texts and codes each verse into four variables: linguistic focus, morphological detail, verse references, and comparative-fiqh discussion. Intertextual analysis à la Julia Kristeva reveals two mechanisms of change: transposition—a shift from semantic exposition to detailed morphological analysis in verses 2-3; and transformation—an expansion of linguistic notes into multi-madhhab fiqh discourse in verses 1, 4, 6 and 7. These shifts were driven by Misbah’s concern over populist taqlīd, the imperative to safeguard ritual purity, and the community’s demand for applicable legal guidance in late-Orde-Baru Indonesia. Consequently, Tāj al-Muslimīn emerges as a more normative and practical tafsīr that reinforces pesantren scholarly authority while enhancing madhhab literacy. The transposition–transformation matrix proposed here offers a fresh heuristic for reading the dynamics of pesantren exegesis and underscores the contemporary relevance of the maqāṣid al-syarīʿah paradigm.